Faktor–Faktor Yang Mempengaruhi Kejadian Hepatitis B Surface Antigen (HBsAg) Reaktif Terhadap Ibu Bersalin di Rumah Sakit TK III Dr. R Soeharsono Banjarmasin 2017 - Ermas Estiyana; Salasiah Supiyati; Nurmilawati Nurmilawati (HB PRESS, 2018)
Hepatitis B disease is liver cells inflammation or infection that caused by the hepatitis B virus. This can be acute or chronic and categorized as the most dangerous liver disease compared to other liver diseasebecause, hepatitis Bis a disease shows less obvious symptoms, it only shows a drops of yellow color on the eyes and the skin and followedby lethargic body. Hepatitis B virus can be found in the body fluids, such as blood, saliva, feces, urine, sperm, and vaginal fluid. In epidemiology,hepatitis B virus can be transmitted in two ways, vertically and horizontally. The disease can be detectedthrough an examination of Hepatitis B Surface Antigen (HBsAg) which is a surface antigen of the hepatitis B virus. This research is aimed to know the factors that influence the incidence of Hepatitis B Surface Antigen (HBsAg) reactive in maternity at the Hospital TK. III Dr. R Soeharsono Banjarmasin in 2017. This research use analytic methods in labour. Based on the results of the statistical tests on several variables by using the chi square, it showed that the age obtained a value of p is 0.003, the behavior obtained the value of p is 0.001, the job obtained on the value of p is 0,016, and the environment obtained value of p is 0.001 which can be concluded that these four variables have an effect on the incidence of Hepatitis B Surface Antigen (HBsAg) Reactive. Therefore, it is expected for the mother in order to reduce the use of sharp objects, household appliances simultaneously and it is expected for them to get the vaccine or treatment for Hepatitis B Surface Antigen (HBsAg) Reactive.